Study of Bullet Impact on Car Glass from Various Guns Sizes At Different Distances and Angles - กุลนิเทศ ผู้ช่วยศาสตราจารย์พิเศษ พลตำรวจโท ดร.ณรง (Journal of Food Health and Bioenvironmental Science, 2019)
This research aimed to study impact patterns caused by different types of bullets discharged from a Luger automatic pistol and a special revolver pistol at different distances and angles. The study also sought to study the relation between trace patterns and distances and angles to support forensic science. This research studied the effects of distances on impact marks on the car’s front windshield, rear-view mirror and side mirror. The firearms selected were popular sidearms used by criminals – 9 mm. Luger automatic (LRN) and .38 Special Revolver (LRN); researchers fired both full metal jacket bullets and lead round nose bullets from each. Selected distances ranged from 1-3 meters and the three selected trajectories were 30°, 45° and 90°, relative to the mirror surface. The research result showed that the kind of bullet and distance did not affect the lateral impact characteristics on laminated or tempered glass. Conversely, it was found that bullet size significantly affected lateral impact characteristics. Moreover, shooting distance resulted in distinct radial fracture characteristics. It was also concluded that radial and concentric fracture characteristics are informative of the caliber of the firearm.